2018
DOI: 10.1101/277020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Reconstructing imagined letters from early visual cortex reveals tight topographic correspondence between visual mental imagery and perception

Abstract: Brain-computer interfaces offer a way to communicate for people with severe motor and speech disabilities. However, successful current letter speller implementations require perception-driven paradigms (EEG) or cognitively demanding tasks (fMRI, fNIRS) which are not directly linked to letters visualized in the mind's eye. A more natural, content-based, BCI speller system immediately decoding imagined letters from associated brain activity is desirable. In the current study, we take the first steps towards such… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The dominant model also provides a principled account of interindividual differences in VMI, because the level of activation in low-level visual areas seem to correlate with the subjective experience of "vividness" of visual mental images 22 . Recent support to this claim came from the finding that the content of VMI can be decoded from V1 activity 58 . However, in all the decoding studies visual stimuli were presented before asking subjects to imagine them.…”
Section: Lack Of Increased Activation In Primary Visual and Motor Cormentioning
confidence: 99%
“…The dominant model also provides a principled account of interindividual differences in VMI, because the level of activation in low-level visual areas seem to correlate with the subjective experience of "vividness" of visual mental images 22 . Recent support to this claim came from the finding that the content of VMI can be decoded from V1 activity 58 . However, in all the decoding studies visual stimuli were presented before asking subjects to imagine them.…”
Section: Lack Of Increased Activation In Primary Visual and Motor Cormentioning
confidence: 99%
“…However, several considerations are also encouraging the pursuit of this goal. First of all, several successful attempts have shown that it is possible to reconstruct presented images from brain activity (Miyawaki et al, 2008;Naselaris, Prenger, Kay, Oliver, & Gallant, 2009;Nishimoto et al, 2011;Schoenmakers, Barth, Heskes, & van Gerven, 2013;Senden, Emmerling, Hoof, Frost, & Senden, 2018;Thirion et al, 2006;van Gerven, Güçlütürk, Seeliger, Ambrogioni, & Güçlü, 2018;St-Yves & Naselaris, 2019). In an important way, the task of reconstructing conscious experience from brain activity is more straightforward than that of reconstructing shown images: By most scientific and by many philosophical accounts of consciousness we should expect all information relevant for conscious experience to be available in the brain (but see O' Regan and Noë, 2001).…”
Section: Reconstructing Conscious Experiencementioning
confidence: 99%
“…By contrast, information about image details are incomplete given that not all aspects of an image are necessarily encoded by our senses (St-Yves & Naselaris, 2019); these aspects of an image can never be recovered from brain activity. Furthermore, a few studies have shown that it is possible to reconstruct imagined images (Naselaris, Olman, Stansbury, Ugurbil, & Gallant, 2015) and letters (Senden et al, 2018) from brain activity. This is particularly encouraging for reconstruction of conscious experience since during imagery no sensory information from the stimulus was available (thus bypassing the demarcation problem).…”
Section: Reconstructing Conscious Experiencementioning
confidence: 99%
See 2 more Smart Citations